Análise teórica e desempenho experimental da nanofiltração de soluções binárias e ternárias de ácido succínico - Díaz, Paola Andrea Borda (2020)
Fermentation is an alternative for the production of dicarboxylic acids on a large scale. However, the fermentation process still needs to be improved. Nanofiltration has been studied as a post-fermentative step to improve purification and intensify the production process. In this work, the transport of a dicarboxylic acid, succinic acid, through nanofiltration membranes was investigated. The effects of gauge pressure, pH, succinic acid concentration and the presence of glucose (as a neutral solute) and salts (NaCl and MgSO4) on acid rejection and permeate flux were evaluated. It has been found that acid rejection increases with pH and can drastically change from <10% at low pH to> 90% at high pH. There is also an increase in rejection as the effective pressure applied increases. The permeate flux increases with effective pressure and, in general, can decrease up to 91% when pH increases from 2.40 to 7.60. However, it was observed that the permeate flux increased or remained constant at pHs close to the isoelectric points due to the absence of the electroviscous effect. Also, at pH values close to the membrane isoelectric point, the increase in the concentration of NaCl and MgSO4 influences the succicnic acid rejection by increasing it. On the other hand, succinic acid rejection is lowered by the presence of MgSO4 at pH of 7.60 due to the screening effect. In addition to the experimental studies, the Maxwell-Stefan approach was applied to describe succinic acid transport of across the nanofiltration membrane, in order to estimate permeate flux and rejection data. The model described well to the experimental results, except for pH values close to the isoelectric point and in ternary systems containing glucose/succinic acid/ water, due to changes in the electroviscous effect, concentration polarization and possible preferential solvation.